« Demanio » o « feudo » ? L’università della Cava tra la signoria monastica e la corona angioina. Centri, periferia e uffici nel Regno di Napoli (XIII-XV) - Massimo Siani (Bulletin du Centre d’Études Médiévales d’Auxerre)
The political and social transformations, started between the end of the XIII and XIV centuries have made a combination of several overlapping layers, where the territory and jurisdiction hardly coincide and where any institution rarely spread over a contiguous area. The origin of the city of Cava (Kingdom of Naples) between the end of the XIII and the middle of XV centuries shows how both characters (royal and monastic-feudal) interacted each other in a specific dialectic between centres – the crown and the monastery of Trinity – and periphery (the universitas of Cava). Royal and feudal privileges are the setting where this investigation works not forgetting what happened concerning Cava, Salerno and the abbey during that period.